The failure of environmental education (and how we can fix it) - Saylan, Charles, 1953- (University of California Press, 2011)
At a time when wild places everywhere are vanishing before our eyes, Charles Saylan and Daniel T. Blumstein offer this passionate indictment of environmental education--along with a new vision for the future. Writing for general readers and educators alike, Saylan and Blumstein boldly argue that education today has failed to reach its potential in fighting climate change, biodiversity loss, and environmental degradation. In this forward-looking book, they assess the current political climate, including the No Child Left Behind Act, a disaster for environmental education, and discuss how educati.